2020
DOI: 10.1177/0972262920926827
|View full text |Cite
|
Sign up to set email alerts
|

User Satisfaction and Continuance Intention for Using E-Training: A Structural Equation Model

Abstract: With the growth in technology, organizations have started investing in building technology infrastructure. The application of technology in enterprises has provided various advantages such as low training cost and reliable training content. This study tries to investigate the attributes influencing user satisfaction and continuance intention to use e-training. The study derives ease of use and course content as the factors that can affect user satisfaction which further results in a user’s intention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…Previous studies have found that satisfaction with e-learning systems leads to students' continued intentional use of the system (Cheng, 2020;Garg and Sharma, 2020). The current study hypothesises that a key determinant of student e-loyalty is online courses' continuance intention which is reflected by students' satisfaction (Song, 2010).…”
Section: E-loyaltymentioning
confidence: 75%
“…Previous studies have found that satisfaction with e-learning systems leads to students' continued intentional use of the system (Cheng, 2020;Garg and Sharma, 2020). The current study hypothesises that a key determinant of student e-loyalty is online courses' continuance intention which is reflected by students' satisfaction (Song, 2010).…”
Section: E-loyaltymentioning
confidence: 75%
“…Al-Gahtani (2016) discovered that PEU positively influences behavioural intention. Most studies have supported the idea that PEU has a positive and significant relationship with BI (Lee et al, 2013;Garg & Sharma, 2020).…”
Section: Peu Pu Cse Pe and Bimentioning
confidence: 98%
“…Lee, Hsieh, and Ma (2011) examined the influence of individual, organizational, and task characteristics, as well as subjective norms as determinants of behavioural intention to use e-learning in an organizational context. Garg and Sharma (2020) found ease of use influenced user satisfaction which resulted in users' intention to continuously use e-training in the workplace.…”
Section: Behavioural Intention To Use E-learning In the Workplace (Bi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Learners will continue to use the proposed IS if they find Elearning beneficial and vice versa [11]. Several studies [31] underpin this relationship between user intention and the success of an IS. In this study, it is expected that learners perceive IS contribution to the improvement of their CT TL performance in the classroom.…”
Section: Learning Supportmentioning
confidence: 99%